Relevance of dissolved organic nutrients for the Arctic Ocean nutrient budget. Issue 12 (23rd June 2016) - Torres‐Valdés, Sinhué; Tsubouchi, Takamasa; Davey, Emily; Yashayaev, Igor; Bacon, Sheldon
Abstract: We ask whether dissolved organic nitrogen (DON) and phosphorus (DOP) could account for previously identified Arctic Ocean (AO) inorganic nutrient budget imbalances. We assess transports to/from the AO by calculating indicative budgets. Marked DON:DOP ratio differences between the Amerasian and Eurasian AO reflect different physical and biogeochemical pathways. DON and DOP are exported to the North Atlantic via Davis Strait potentially being enhanced in transit from Bering Strait. Fram Strait transports are balanced. Barents Sea Opening transports may provide an additional nutrient source to the Barents Sea or may be locked within the wider AO Atlantic Water circulation. Gaps in our knowledge are identified and discussed. Key Points: There are marked differences in the DON:DOP ratio between the Eurasian and Amerasian Arctic Ocean The Arctic Ocean exports DON and DOP to the North Atlantic Lack of observations hinder the ability to resolve temporal changes in nutrient transports and budgets